The Impact of COVID-19 on Learning and School Readiness of Children Aged 0-8 Years - Tumwesigye, Keneth (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2026)
This study aimed to understand the connection between reception of children aged 0-8 years experiences of the COVID-19 pandemic and their academic achievements in regards to reading, writing, numbers and school readiness. This was an exploratory study which combined parents, caregivers, and teachers’ surveys with children’s assessments to measure children’s language, numeracy and social emotional development. Comparisons were made between the scores of children in study programs in the previous years before the outbreak of COVID-19 pandemic. This study employs a scoping review of latest systematic literature reviews consisting of a review of reviews and meta-analysis studies on the impact of COVID-19 pandemic on children aged 0 - 8 years.